La investigación metateórica en bibliotecología (La Rivada, 2024)
The usefulness of metatheoretical research in library science is examined as a crucial tool to clarify the epistemological position of the discipline, investigating its object of study, methods, underlying theories, and its legitimacy within the academic and professional communities. It is argued that understanding the underlying epistemology in library science is fundamental for the development and improvement of the discipline, as well as for the advancement of knowledge in general.   Some aspects characterizing the metatheoretical development experienced by the discipline in Argentina in recent years are analyzed, within the framework of a research project on the Documentary Information Metasystem, developed at the Universidad Nacional de Misiones.   It is concluded that the metatheory of library science in the national scope has had uneven but progressive advancement; however, there are obstacles and challenges that must be overcome in order to consolidate itself.
Keywords: Library science; metatheorical research; Argentina